Understanding Motivation, Career Planning, and Socio-Cultural Adaptation Difficulties as Determinants of Higher Education Institution Choice Decision by International Students in the Post-pandemic Era - Zuo, Kun (Frontiers in Psychology, 2022)
The world is facing an unprecedented health crisis with the spread of COVID-19 across different corners of the globe. This pandemic has raised more significant concerns about international students’ learning environment, personality development, and career planning, particularly in high-ranked institutes in China. Now the question concerning this dilemma is, would the COVID-19 pandemic negatively affect students’ education and the country culture where they are bound to seek information and the subject education? Therefore, this study examines the impact of innovative learning environment, career planning, and socio-cultural adaptation-related difficulties faced by international students as determinants of higher education institution choice decisions made by international students in the post-pandemic era. This quantitative study examined international students in high-ranked universities across China. The data from 260 students were collected through a structured questionnaire and analyzed using the AMOS technique. Moreover, it has been observed that the current global health crisis has intensified social inequalities across different international higher education systems. Countries fail to maintain the scale of the innovative international learning environment. The results further indicated that international students are more considerate of innovative learning environments, cultural adoption, career planning, and personality development, specifically after the outbreak of the COVID-19 pandemic, which has drastically affected the global higher education system. Unusually, more than half of the participants wanted to maintain the option of overall distance education after the pandemic. However, apart from this argument, it is appropriate to demand significant changes in post-pandemic education adapted to the post-digital era and to satisfy the concerns and expectations of the students.